Penyelarasan Strategi Teknologi Informasi dan Strategi Bisnis dalam Kerangka Universitas 4.0 di STT Pagar Alam - Risnaini Masdalipa; Muhammad Izman Herdiansyah; A. Haidar Mirza (UNIVERSITAS INDO GLOBAL MANDIRI)
Business activities in a company or institution currently have high competition. Companies are not only required to have a business strategy. Along with the development of information technology, companies must also develop an information system strategy based on the business strategy that the company has developed. The purpose of designing business strategies and information systems strategies is to strengthen the strength of competitiveness in the technological era by implementing strategic information systems by considering and aligning business strategies in accordance with the conditions of the strength of the company or college. The use of IT in STT Pagar Alam as a whole has not been implemented but some have been implemented both from the network, the management system, and even to the teaching system already using IT. This study aims to analyze the alignment of information technology and business strategies in STT Pagar Alam using the IT Balanced Scorecard framework. The results of the analysis of this study stated that the initial step in designing the IT Balanced Scorecard at STT Pagar Alam is to align the vision, mission, and strategy of a tertiary institution. Determined objectives to determine the strategic size of each strategic goal. The results of this study are that the use of IT in STT Pagar Alam as a whole has not been implemented and produced a strategic map that is classified from four perspectives in the IT Balanced Scorecard associated with IT strategy. Keywords : Analysis, IT strategy, IT Balanced Scorecard.